Case Report: Primary Cardiac T-Cell Lymphoma With Complete Atrio-Ventricular Block Diagnosed by Endomyocardial Biopsy - Chen, Panpan; Hao, Yuanyuan; Qiu, Xi; Xiao, Xibin; Zhu, Wei; Xu, Yang; Qian, Wenbin (Frontiers in Immunology, 2022)
Primary cardiac lymphoma (PCL) is a rare disease, the definite diagnosis of which is sometimes difficult and mainly relies on endomyocardial biopsy. Primary cardiac T-cell lymphoma (PCTL) is an extremely rare sub-type of PCL. Here, we report a 47-year-old female with PCTL who presented with fever, syncope, palpitations and a third-degree atrioventricular block (AVB) on electrocardiogram. Chemotherapy was administered with two courses of methotrexate, cyclophosphamide, liposomal doxorubicin, vincristine, and dexamethasone (MTX-CHOP). As the tumor vanishing, AVB changed from third degree to second degree and finally to sinus rhythm. In conclusion, endomyocardial biopsy is valuable in the diagnosis of primary cardiac lymphoma. It is worth noting that alterations in the electrocardiogram may indicate an attack on the heart by PCTL.